2022
DOI: 10.1093/sf/soab165
|View full text |Cite|
|
Sign up to set email alerts
|

Patterns of Perceived Hostility and Identity Concealment among Self-Identified Atheists

Abstract: Researchers have produced important findings regarding the types of stigma associated with nonreligion, particularly atheism. However, while numerous studies analyze who is more or less likely to identify as an atheist given that stigma, less is known about how self-identified atheists manage the stigma associated with their identity. This study uses new survey data from a nationally representative sample of US adults, with an oversample of individuals identifying as atheists, to examine the predictors of and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Though participants were aware of these and other anti-atheist biases, they had infrequent direct experiences of discrimination and anti-atheist stigma did not drive their decisions regarding outness. Frost et al (2022), too, found no relation between atheists’ perceptions of hostility toward their atheist identity and their concealment of that atheist identity, though women did conceal more as compared to men. They suggested atheists who perceived themselves as social or institutional outsiders were more likely to conceal.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Though participants were aware of these and other anti-atheist biases, they had infrequent direct experiences of discrimination and anti-atheist stigma did not drive their decisions regarding outness. Frost et al (2022), too, found no relation between atheists’ perceptions of hostility toward their atheist identity and their concealment of that atheist identity, though women did conceal more as compared to men. They suggested atheists who perceived themselves as social or institutional outsiders were more likely to conceal.…”
Section: Discussionmentioning
confidence: 84%
“…Atheists, particularly those belonging to other marginalized communities (e.g., people of color and low-income atheists), engage in a process of strategic outness (see Orne, 2011) in which they exercise caution with regard to disclosure of their atheism and use concealment to protect relationships, avoid negative consequences in the workplace, and ensure emotional and physical safety (Abbott et al, 2020a;Abbott et al, 2021). Indeed, Frost et al (2022) found women were more likely to conceal their atheism as compared to men. In a crossnational study of feminist, atheist women, participants described methods of making their atheism and feminism palatable to others, thus avoiding aggression and balancing femininity (Trzebiatowska, 2019).…”
Section: Anti-atheist Discriminationmentioning
confidence: 99%
“…This suggests that nonreligious individuals face social identity threat (Steele et al, 2002). Because atheists and other nonreligious individuals are aware of the stigma attached to their identity, they may distance themselves from the “atheist” label (Scheitle et al, 2019) or conceal their nonreligious identity entirely (Frost et al, 2023; Mackey et al, 2021). That is, there may be less overlap between nonreligious individuals’ public expression of identity and private expression of identity in religious contexts.…”
Section: Religious Contexts Of the United States The Netherlands And ...mentioning
confidence: 99%
“…Under certain political situations, the prejudice in societies against atheists may rise. For example, in the U.S. in the second half of the 20 th century atheism was seen as anti-American and pro-communist (Frost, Scheitle, Ecklund, 2022). Even nowadays, together with Muslims and homosexuals, atheists are among the most disliked minorities in the U.S. (Weiler-Harvell, 2011: 2).…”
Section: Societal Impact Of Negative Labellingmentioning
confidence: 99%